Millimeter wave antennas for 5G mobile terminals and base stations - Koul, Shiban Kishen; Karthikeya, G.S. (London: CRC Press, 2021)
"This book gives a comprehensive idea of the recent research efforts targeting mmWave 5G mobile terminals and base stations. This is followed by conformal antennas which could be easily integrated onto typical smartphones"--